Bioconversion of different organic waste into fortified vermicompost with the help of earthworm: A comprehensive review - Sharanpreet Singh; Jaswinder Singh; Alkesh Kandoria; Jahangeer Quadar; Sartaj Ahmad Bhat; Anu Bala Chowdhary; Adarsh Pal Vig (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Solid waste management has become a serious global problem. There is a strong need to recycle them as these wastes are rich in plant nutrients and soil conditioners. The different organic wastes can be efficiently degraded into nutrient-rich vermicompost by using earthworms. In this review, an attempt has been made to highlight the vermicomposting of different organic wastes by using different earthworm species. Methods An extensive literature search was done on Science Direct, Pubmed Central, Google Scholar, Springerlink by using various search strings, and appropriate studies of vermicomposting of different organic waste were selected. Results Any kind of organic waste can be converted into manure through vermicomposting. It was observed that for efficient vermicomposting, the waste should be mixed with another organic material. e.g., animal dung. It was observed that the vermireactors having 25 % to 30 % of waste mixed with about 70 % to 75 % of other organic rich material like cattle dung can be easily converted into a valuable product, but the high proportion of organic waste causes mortality in the earthworms. Conclusion This study indicated that vermicomposting is an effective and a better option for the recycling of different types of organic solid waste but these wastes cannot be directly degraded with the help of earthworms.  The vermicompost so produced can be used to promote the growth of wide range of crops in the fields. The farmers should also be educated regarding the harmful effects of chemical fertilizers and pesticides and also get motivated to use vermicompost in their fields.